FRAKTUR PADA TULANG MAKSILA - Pratiwi Suardi, Ni Putu Enny; Asmara Jaya, AA GN; Maliawan, Sri; Kawiyana, Siki (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Trauma is the leading cause of death in human. Some human occasionally sustain severe injuries of the face which requires appropriate therapy. Maxillofacial trauma, is any physical trauma to the face. Facial trauma can involve soft tissue injuries such as burns, lacerations and bruises, or fractures of the facial bones such as nasal fractures and fractures of the jaw, as well as trauma such as eye injuries. Symptoms are specific to the type of injury; for example, fractures may involve pain, swelling, loss of function, or changes in the shape of facial structures. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman";}
Keywords: maxillofacial trauma, fractures of the facial bones